2015
DOI: 10.1155/2015/710328
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Calcium Compounds inOpuntia ficus indicaas a Source of Calcium for Human Diet

Abstract: Analyses of calcium compounds in cladodes, soluble dietary fiber (SDF), and insoluble dietary fiber (IDF) ofOpuntia ficus indicaare reported. The characterization of calcium compounds was performed by using Scanning Electron Microscopy, Energy Dispersive Spectrometry, X-ray diffraction, and infrared spectroscopy. Atomic Absorption Spectroscopy and titrimetric methods were used for quantification of total calcium and calcium compounds. Whewellite (CaC2O4·H2O), weddellite (CaC2O4·(H2O)2.375), and calcite (CaCO3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…In the case of the present study the most significant changes in microstructure were observed in trabecular and cortical bones. Figure 2 shows that N-200 was the least effective sample in providing absorbable calcium, this is probably due to a combination of several factors that include: (a) a lower level of soluble dietary fiber (SDF), which is known to facilitate calcium absorption; and (b) a variation in content of bioavailable calcium salts, which are associated to SDF, as was previously reported by our research group [ 10 , 11 ]. Microstructural characteristics of the femurs were positively related to the mechanical properties.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In the case of the present study the most significant changes in microstructure were observed in trabecular and cortical bones. Figure 2 shows that N-200 was the least effective sample in providing absorbable calcium, this is probably due to a combination of several factors that include: (a) a lower level of soluble dietary fiber (SDF), which is known to facilitate calcium absorption; and (b) a variation in content of bioavailable calcium salts, which are associated to SDF, as was previously reported by our research group [ 10 , 11 ]. Microstructural characteristics of the femurs were positively related to the mechanical properties.…”
Section: Discussionmentioning
confidence: 56%
“…Opuntia ficus indica cladodes were cultivated in an experimental field in Silao, Guanajuato (Rancho Los Lorenz), México, with organic fertilizer harvested during the spring of 2015. The O. ficus indica cladodes at 25, 60, 100 and 135 days of maturation stage (weighing 60, 200, 400 and 600 g, respectively) were dehydrated as previously reported [ 10 ]. The experimental diets (N-60, N-200, N-400, N-600 and control) were prepared with American Institute of Nutrition Rodent Diets for growing rats (AIN-93G) [ 13 ] with modifications ( Table 1 ) including the addition of vitamin mix (AIN-93-VX, Harlan Inc., Indianapolis, IN, USA, TD 94047) and mineral mix without calcium (AIN-93-MX, Harlan Inc., TD 04374).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sparser occurrence of calcium oxalate crystals may be beneficial to consumer health, influence the lower Ca content of O. robusta cladodes ( Table 3 ) and have an influence on the viscosity of the mucilage [ 5 ]. Nevertheless, no calcium oxalate crystals were observed in any of the dried mucilage samples, possibly due to the low solubility of calcium oxalate and the relatively low concentration of calcium oxalate found in soluble fibre [ 25 ]. It may be deduced that the calcium oxalate crystals did not co-extract when the mucilage was separated from the solids during the extraction process.…”
Section: Resultsmentioning
confidence: 99%
“…Values of 3.4/100 g [ 21 ] and 3.6/100 g [ 30 ] compared well with mean Ca values reported in this study. Ca is bioavailable as the oxalate: calcium ratio is ≥1 [ 25 ] in cladodes. The consumption of young cladodes (nopalitos) increase Ca intake in the diet [ 13 ].…”
Section: Resultsmentioning
confidence: 99%